Achieving environmental sustainability with ecodesign practices and tools for new product development - Jugend, Daniel [UNESP]; Pinheiro, Marco Antonio Paula [UNESP]; Luiz, João Victor Rojas [UNESP]; Junior, Angelo Varandas; Cauchick-Miguel, Paulo Augusto (Elsevier, 2019)
Ecodesign is recognized as the practice of reducing environmental impacts in the early phases of new product development (NPD) as well as the product life cycle. It contributes to the development of environmentally sustainable products (eco-friendly products) and thus to environmental sustainability. Nevertheless, studies have pointed out difficulties in adopting ecodesign for practitioners and scholars. To contribute to this subject, this chapter discusses ecodesign practices and tools from three NPD perspectives. The first emphasizes the importance of integrating ecodesign in the process of NPD and product portfolio decision-making. The second perspective deals with methods and tools that foster practical applications of ecodesign, such as environmental quality function deployment; the materials, energy, and toxicity matrix; and the ecodesign checklist. Third, predominant issues that motivate ecodesign are discussed in addition to some barriers to adopting it. This chapter also describes some examples of ecodesign research and applications in Brazilian companies.
Keywords: Circular economy; Eco-innovation; Ecodesign; New product development; Stakeholders; Sustainable design